Roberto Marín Guzmán's contributions to the history of the Middle East and North Africa - Barrientos Valverde, Jorge Ezequiel (2024)
Biography of Dr. Roberto Marín Guzmán (Ciudad Quesada 1955-San José 2024, Costa Rica)